Yahoo Web Search

  1. Sort by

  1. ...2 X^2 = C where C is an arbitrary constant The LHS is the sum of two squares so C > 0. It's...

    2 Answers · Science & Mathematics · 27/12/2009

  2. ...gal )( 10 gal/min ) dQ/dt = -10Q / 55 Move Q to the LHS and then integrate ∫ 1/Q dQ = -10/55 ∫ dt ln Q = -10t/55...

    2 Answers · Science & Mathematics · 11/12/2009

  3. Q>0 & Q'>0 & K>0 & L>0 LHS ~ RHS Q ~ Q' 10•K^(0.5)•L^(0.5) ~ 10...

    1 Answers · Science & Mathematics · 19/11/2009

  4. ...on the left hand side should be equal to the values on the right hand side. LHS=((A+.(B.C) A.C+B))’ RHS=A...

    1 Answers · Science & Mathematics · 22/09/2012

  5. y1'(t) = 0 y2'(t) = 3(t-t0)^2 Then, for y1: LHS: y'(t) = 0 RHS: 3y^(2/3) = 3(0)^(2/3) = 0 ✓ And for y2: LHS: y'(t) = 3(t-0)^2 = 3t^2 RHS: 3y^(2/3) = 3[(t-0)^3]^(2/3) = 3t^2 ✓

    1 Answers · Science & Mathematics · 30/09/2009

  6. Assuming that the left hand support (LHS) is pinned then take moments about the LHS RHS...

    2 Answers · Science & Mathematics · 13/09/2009

  7. ...1/tanA = cotA sin(2A) = 2 * sinA * cosA LHS tanA + cotA RHS 2/(2 sinA * cosA) =...

    1 Answers · Science & Mathematics · 29/07/2009

  8. ...^-1 x X Since A^-1 A = E (unit matrix) LHS = E X = X RHS = x A^-1 X Or...

    2 Answers · Science & Mathematics · 07/04/2009

  9. ...(wt) and both integrals go from t = 0 to t = t The LHS integrates as: Vout(t) - Vc(0) where Vc(0) ...

    6 Answers · Science & Mathematics · 18/10/2008

  10. ...rank-6 solutions. 1. Get the RHS variables to the LHS and incorporate it into your problem: i,e, define X = [x,y,z,n1,n2,n3,n4...

    5 Answers · Science & Mathematics · 02/11/2007

  1. Try asking your question on Yahoo Answers